2000
DOI: 10.1093/oxfordjournals.molbev.a026330
|View full text |Cite
|
Sign up to set email alerts
|

On the Origin and Domestication History of Barley (Hordeum vulgare)

Abstract: Remains of barley (Hordeum vulgare) grains found at archaeological sites in the Fertile Crescent indicate that about 10,000 years ago the crop was domesticated there from its wild relative Hordeum spontaneum. The domestication history of barley is revisited based on the assumptions that DNA markers effectively measure genetic distances and that wild populations are genetically different and they have not undergone significant change since domestication. The monophyletic nature of barley domestication is demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
366
1
9

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 550 publications
(414 citation statements)
references
References 24 publications
16
366
1
9
Order By: Relevance
“…The genetic relationships among the taxa considered were established using the phylogenetic analysis package PHYLIP (Felsenstein 1989) and the multivariate analysis system NTSYS (Rohlf 1998). For the phylogenetic analysis concerning AFLP allele frequencies in populations or groups of lines, ten independent trees were constructed as described (Heun et al 1997;Badr et al 2000), using CONTML and distance matrix methods (Fitch and Margoliash 1967;Saitou and Nei 1987), and employing various measures of genetic distance (Cavalli-Sforza and Edwards 1967;Nei 1972;Wright 1978;Reynolds et al 1983) calculated from AFLP allele frequency. To cluster single accessions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic relationships among the taxa considered were established using the phylogenetic analysis package PHYLIP (Felsenstein 1989) and the multivariate analysis system NTSYS (Rohlf 1998). For the phylogenetic analysis concerning AFLP allele frequencies in populations or groups of lines, ten independent trees were constructed as described (Heun et al 1997;Badr et al 2000), using CONTML and distance matrix methods (Fitch and Margoliash 1967;Saitou and Nei 1987), and employing various measures of genetic distance (Cavalli-Sforza and Edwards 1967;Nei 1972;Wright 1978;Reynolds et al 1983) calculated from AFLP allele frequency. To cluster single accessions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…c Genetic relationships of domesticated tetraploid wheats with wild T. dicoccoides groups sampled in different regions of the Fertile Crescent with origins already specified in b. Using programs of the PHYLIP package (1993), 10 independent trees were constructed as described (Heun et al 1997;Badr et al 2000) using CONTML (topology shown; Felsenstein 1981) and distance matrix methods (Fitch and Margoliash 1967;Saitou and Nei 1987) employing various measures of genetic distance (Cavalli-Sforza and Edwards 1967;Nei 1972;Wright 1978;Reynolds et al 1983) calculated from AFLP allele frequencies between groups of lines from the geographic regions indicated. The number of tree-buiding methods generating the same topologies is indicated at branches.…”
Section: Resultsmentioning
confidence: 99%
“…Surveys of Adh1 and Bkn-3 found low diversity levels of roughly 0n1 % to 0n2 % (Badr et al, 2000 ;Cummings and Clegg, 1998 ;Petersen and Seberg, 1998). Diversity levels were roughly the same in both the domesticated and wild subspecies for these loci.…”
Section: How Has DI Ersity Changed During Domestication?mentioning
confidence: 98%
“…Genome-wide based evidence resoundingly supported the notion on single origins for many crops (e.g. Heun et al, 1997, Badr et al, 2000, Matsuoka et al, 2002 by producing phenograms in which domesticated crops were monophyletic. This data was sometimes in conflict with single gene evidence, such as in the case of barley, which became awkward anomalies to what was largely taken as genetic support for the rapid transition paradigm, and a picture of explosive expansion of agriculturalists out of the centres of origin.…”
Section: Genetic Analysis Within the Rapid Transition Paradigmmentioning
confidence: 98%